Burden and social support in informal caregivers of people undergoing kidney dialysis: a mixed study - Ingrid Fernanda de Oliveira Vieira; Ana Cláudia Mesquita Garcia; Tábatta Renata Pereira Brito; Rogério Silva Lima; Denismar Alves Nogueira; Eliane Garcia Rezende; Silvana Maria Coelho Leite Fava (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the burden and the social support of the informal caregivers of people undergoing kidney dialysis. Methods: mixed study, based on the Theory of Stress and Overload, using instruments of sociodemographic characterization, the Social Support Survey from the Medical Outcomes Study, Zarit's Burden Scale, and guiding questions. Analysis of data used statistical and thematic inferences. Results: 55 caregivers were evaluated, most were women, from 31 to 50 years old, married, and having worked in care for more than three years. A high level of affective and material support was observed, with a light overload on the caregiver. The central theme of the discourses was: "Experiences of the caregiver: between the burden of responsibility and the search for meaning". Conclusions: a small overload was found in the participants, with a high median in the dimensions of affective and emotional support, in the relations between positive social interactions and the burden of the caregivers, in addition to the duality or responsibility and the meaning of care.